2022
DOI: 10.1523/jneurosci.1372-22.2022
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Fluorescence Analysis Reveals Dendrite-Specific Thalamocortical Plasticity in L5 Pyramidal Neurons during Learning

Abstract: High-throughput anatomic data can stimulate and constrain new hypotheses about how neural circuits change in response to experience. Here, we use fluorescence-based reagents for presynaptic and postsynaptic labeling to monitor changes in thalamocortical synapses onto different compartments of layer 5 (L5) pyramidal (Pyr) neurons in somatosensory (barrel) cortex from mixed-sex mice during whisker-dependent learning (Audette et al., 2019). Using axonal fills and molecular-genetic tags for synapse identification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 75 publications
(137 reference statements)
1
8
0
Order By: Relevance
“…The large postsynaptic nanoscale features of L5 TC synapses are consistent with work showing relatively strong TC synaptic currents on basal dendrites of L5 neurons [55]. Selective enlargement of L5A inputs and associated PSD-95 has been recently linked to experience-dependent plasticity [71]. It will be essential to determine whether TC synapses on basal dendrites lack mGluR nanodomains, a characteristic feature of glutamatergic drivers [70].…”
Section: Discussionsupporting
confidence: 68%
“…The large postsynaptic nanoscale features of L5 TC synapses are consistent with work showing relatively strong TC synaptic currents on basal dendrites of L5 neurons [55]. Selective enlargement of L5A inputs and associated PSD-95 has been recently linked to experience-dependent plasticity [71]. It will be essential to determine whether TC synapses on basal dendrites lack mGluR nanodomains, a characteristic feature of glutamatergic drivers [70].…”
Section: Discussionsupporting
confidence: 68%
“…Over the course of several days, animals learn to associate a whisker stimulus with a water reward, measured by an increase in lick frequency to stimulus compared to “blank” trials (Figure 1F). Prior studies have shown that this sensory association training (SAT) is whisker-dependent (Bernhard et al, 2020) and also drives rapid changes in thalamocortical synaptic strength (Audette et al, 2019; Ray et al, 2023), indicating that this training is sufficient to initiate both synaptic and behavioral plasticity. Across the population of trained SST-Cre animals, mice showed a significantly greater lick frequency in stimulus versus “blank” trials after just 1 day of SAT (Figure 1G; 6.3±0.5Hz versus 5.6±0.5Hz).…”
Section: Resultsmentioning
confidence: 99%
“…It has been proposed that increasing inhibition is critical during excitatory synaptic plasticity in order to maintain some balance of excitation and inhibition (Barron, 2021; Okun and Lampl, 2008; Vogels et al, 2011), but these hypotheses have not articulated a source or a target for this inhibition, nor the timescale at which this balancing plasticity should occur. Prior studies have shown that SAT drives the potentiation of both thalamocortical and intracortical excitatory synapses (Audette et al, 2019; Ray et al, 2023). These new data indicate that at least at the early stages of learning, in this task and for L2 Pyr neurons, the potentiation of excitatory synapses is not accompanied by an increase in SST-mediated inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…To test whether pyramidal-cell-derived BMP2 modifies the innervation of PV interneurons, we generated Bmp2 conditional knockout mice in whi ch Bmp2 is selectively ablated in upper-layer glutamatergic neurons ( Cux2 creERT2 ::Bmp2 fl/fl ; referred to as Bmp2 ΔCux2 mice). We then adopted genetically encoded intrabodies (fibronectin intrabodies generated by mRNA display; FingRs) to quantitatively map the synaptic inputs to PV interneurons 39 , 40 (Extended Data Fig. 6a–c and Supplementary Video 1 ).…”
Section: Smad1 Controls the Innervation Of Pv Interneuronsmentioning
confidence: 99%